Fatigue predicts quality of life after leucine‐rich glioma‐inactivated 1‐antibody encephalitis - Sophie Binks; Michele Veldsman; Adam E. Handel; Saiju Jacob; Paul Maddison; Jan Coebergh; Sophia Michael; Sudarshini Ramanathan; Ava Easton; Mette Scheller Nissen; Maria Isabel Leite; David Okai; et al. (2024)
Patient-reported quality-of-life (QoL) and carer impacts are not reported after leucine-rich glioma-inactivated 1-antibody encephalitis (LGI1-Ab-E). From 60 patients, 85% (51 out of 60) showed one abnormal score across QoL assessments and 11 multimodal validated questionnaires. Compared to the premorbid state, QoL significantly deteriorated (p < 0.001) and, at a median of 41 months, fatigue was its most important predictor (p = 0.025). In total, 51% (26 out of 51) of carers reported significant burden. An abbreviated five-item battery explained most variance in QoL. Wide-ranging impacts post-LGI1-Ab-E include decreased QoL and high caregiver strain. We identify a rapid method to capture QoL in routine clinic or clinical trial settings.